Utilization of flour from off-grade unripe cavendish banana in noodles and baked products - Alviola, Juma Novie A. (Banwa, 2019)
The abundance of off-grade Cavendish bananas may translate into an abundance of nutrient-dense and gluten-free banana flour. This study determined the optimum level of unpeeled (UUBF) and peeled unripe banana flour (PUBF) that can be substituted for wheat flour in egg noodles, chiffon cake, and tart shell. The UUBF had high resistant starch (RS) at 65.34%, crude ash at 3.78%, and fiber content at 1.99%; on the other hand, the PUBF had 59.55% RS, 1.83% ash, and 0.97% fiber. Egg noodles with 20% UUBF were darker and weaker than the control but were the most preferred formulation. This had significantly higher crude as (2.94%) and RS content (17.72%) than the control, and both samples were “liked moderately.” Moreover, the UUBF caused no significant change in the noodles’ cooking properties. On the other hand, PUBF was incorporated in the chiffon cake and tart shells. Chiffon cakes with PUBF were significantly darker and less firm than the control. The 40% PUBF cake had higher specific volume, lower density, and higher fiber (0.80%) than the control, but both cakes were “liked very much.” Tart shells with PUBF also became darker and more crumbly. The control and 30% PUBF tart shells were both “liked very much” for texture, flavor, and overall acceptability. The latter had significantly higher ash and RS contents (1.39% and 2.19%). These results show that incorporation of UBF generally have no negative impact on consumer acceptability and improved the nutritional content of the products. The use of locally available crops, like banana, for flour production has the potential of lowering the dependence on imported wheat flour.